Any Portal in a Storm? Collaborative and crowdsourced maps in response to Typhoon Yolanda/Haiyan, Philippines - Turk, Catherine (Journal of Contingencies and Crisis Management, 2020)
The promises of crowdsourcing volunteered geographic information (VGI) for providing timely information about crises were recognized at least a decade ago. While cartographers and developers hone the accuracy of maps and data, social scientists critique these technologies through various theoretical lenses: in terms of knowledge politics of digital humanitarianism; as tools of neoliberal governance; and as examples of datification supporting automated or remote government. Amidst all these claims, it is time to return to the maps themselves, as empirical examples, considering the information they actually provide. This paper examines crowdsourced and collaborative maps from late 2013 following Typhoon Yolanda/Haiyan in the Philippines. Various humanitarian, mapping, and media organizations produced maps in response to the typhoon. Close qualitative analysis of map content queries what these maps reveal about the disaster and whether the maps really produce the information that proponents claim. Analysis of data curated in each map reveals that much of the situational information being mapped is already available elsewhere and that few new ground truths have emerged through these projects. By demonstrating the limitations of the information mediated in these maps, the findings have practical and policy implications for disaster practitioners and digital volunteers intending to help disaster response.
CRIS-Team Scopus Importer:2020-11-06
Keywords: critical cartography; crowdsourcing; digital humanitarians; disaster response; volunteered geographic information

Crisis and conflict maps in the Web 2.0: A critical look at the new crisis and conflict maps - Michel, Boris; Bittner, Christian; Glasze, Georg; Turk, Catherine (Geographische Rundschau, 2011)

Crisis Mapping – Eine empirische Untersuchung zu Strukturen und Praktiken partizipativer Krisen- und Konfliktkartographien während der Umbrüche in Libyen und Syrien 2011-2013 - Schmitt, Michael; Gottschlich, Florian; Schäfer, Wolfgang; Turk, Catherine; Glasze, Georg (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2014)

Krisen- und Konflikt-Karten im Web 2.0. Ein kritischer Blick auf die neuen Krisen-und Konfliktkarten - Bittner, Christian; Glasze, Georg; Michel, Boris; Turk, Catherine (Geographische Rundschau, 2011)
UnivIS-Import:2015-04-14:Pub.2011.nat.dgeo.IG.zentr.krisen

Tracing contingencies: Analyzing the political in assemblages of web 2.0 cartographies - Bittner, Christian; Glasze, Georg; Turk, Catherine (Geo Journal, 2013)
Our paper presents a theoretical approach to critical research on web 2.0 cartographies. Within the geoweb, dynamic and collaborative web based maps have become a popular medium for collating and communicating geographic information. Web 2.0 cartographies are often promoted as facilitating public participation and democratizing geographic knowledge. Such claims demand a closer look at the processes through which people do engage in these cartographic projects and the multiple actors, institutions, norms and technologies at work. In the context of 'theorizing the geoweb', here we propose conceptual tools for analyzing these myriad interactions within web 2.0 cartographies. We understand web 2.0 cartographies as assemblages of subjects, materialities and practices, or 'actor networks'. Yet explorations of actor-networks describe existing relations and as a consequence tend to overlook what has been excluded or lies outside of such assemblages. In order to overcome this blindness we suggest bringing together actor-network theory with the concepts of hegemonic discourses, contingency and the political from Chantal Mouffe and Ernesto Laclau. These two political theorists stress the idea that specific social realities become fixed, sedimented and perceived as natural while other possible social realities become marginalized. Using the example of the dynamic 'Palestine Crisis Map' (an Ushahidi Crowdmap) we demonstrate a methodology that emphasizes sensitivity towards moments of exclusion and struggle, where the political unfolds. Theorizing the political in this way extends the processual approach within Critical Cartography and offers a conceptual basis for critical research on the social dimensions of web 2.0 cartographies and geoweb practices. © 2013 Springer Science+Business Media Dordrech
Keywords: Actor-network theory; Critical cartography; Geoweb; Theory of discourses and hegemonies; Web 2.0 cartography

Turning the spotlight on the crowd: examining participatory ethics and practices of crisis mapping - Michel, Boris; Turk, Catherine; Bittner, Christian (ACME : An International e-Journal for Critical Geographies, 2016)